Heuristic approaches for a practical lot splitting and scheduling problem - Pimentel, Carina (2012)
In this talk we present some heuristic approaches for a real world lot splitting and scheduling problem of a Textile factory. The problem consists of finding a weekly production plan for the knitting section of the company, establishing the quantities to produce of each component (organized in one or several lots), and where and when (starting/completion times) to produce them. Two important objectives to achieve are on time delivery of products and minimum levels of work-in-process inventory. We present some results for a set of randomly generated instances based on real world data.